A novel dual-PCM configuration to improve simultaneous energy storage and recovery in triplex-tube heat exchanger. (1st May 2022) - Mozafari, M; Lee, Ann; Cheng, Shaokoon
Highlights: Simultaneous energy storage and recovery is studied for dual-PCM configurations. Solidification behavior is as significant as the melting behavior. Natural convection and melting temperature are crucial for an optimum design. Adding nanoparticles accelerates heat transfer, but decreases the storage capacity. Novel dual-PCM design is better than a single-PCM unit enriched with nanoparticles. Abstract: A novel triplex-tube heat exchanger (TTHX) is proposed to improve the simultaneous storage and recovery processes via an effective dual-PCM configuration. The proposed design achieves better storage and recovery compared to the application of aluminum oxide (Al₂O₃) nanoparticles of 1% or 3% volume fraction with a single-PCM configuration. The storage/recovery system contains two sections holding PCMs with equal volumes but different melting points. Different dual-PCM configurations are examined and compared for two different scenarios of initially fully melted or solidified conditions. A numerical model is developed and validated against existing data. The results show that employing an optimum arrangement of dual-PCMs can improve the rate of melting and solidification in the TTHX under simultaneous charging and discharging (SCD). A configuration with radial separation of PCMs is found to be ideal to accelerate both melting and solidification, such that the PCM with lower melting temperature is housed close to the hot tube. In that case, 23.43%, and 18.87% enhancement is achieved in energy storage and recovery, respectively, compared with the reference case. A parametric optimization reveals that significant improvement could be achieved by applying an upward eccentricity of 17 mm to the radial sector of the selected configuration. In 3 h SCD process with initially solidified/melted conditions in TTHX, the new design enhances the thermal energy storage and recovery as 37.93%, and 21.06%, respectively, which could be further improved to 76.9% in storage and 32.9% in recovery by adding 3% nanoparticles.